CHIME dating of monazite, xenotime and zircon in graphitic schist, Isua Supracrustal Belt, Greenland and problem for the measurement - 大友, 陽子; 79184; 加藤, 丈典; 79185; Ohtomo, Yoko; 79186; Kato, Takenori; 79187 (名古屋大学宇宙地球環境研究所, 2018)
2018-03-31 Biogenic graphite in > 3.7 Ga metasediments, Isua Supracrustal Belt (ISB), West Greenland, has been reported as the oldest remnants of life. However, ecosystem spreaded in the >3.7Ga ocean is still poorly understood. Isua biogenic graphite is located in chlorite-rich layers of metasediments as grains accompanied by monazite, xenotime and zircon. These rare earth element (REE)-bearing minerals could be supplied to sediments at primary sedimentary setting or precipitated from metamorphic fluids. Chemical Th-U-total Pb Isochron Method (CHIME) dating was conducted on these REE-bearing minerals to constraint the generation process. CHIME age of zircon in graphite-rich metasediments indicates 3.9−3.8 Ga, which is consistent with previous zircon age in banded iron formation collected close to our sampling area. CHIME age of monazite and xenotime indicate two age peaks of ~2.7 Ga and ~3.7 Ga. Previous studies suggest that Isua retrograde metamorphism has occurred at ~2.7 Ga (Frei et al., 2001), which is consistent with one of age peaks of monazite and xenotime. Nano-scale observation of monazite by transmission electron microscope showed that well-ordered, sheeted graphite was crystalized around monazite, whereas quartz and disordered graphite were observed as inclusion of monazite. Considering with CHIME results and nano-structures of monazite together, monazite was considered to be formed during early diagenesis with involving indigenous biogenic organic matter and quartz and suffered by subsequent metamorphic events. The occurrence of monazite resembles REE-bearing minerals observed in Australian Archaean sedimentary rocks reported by Rasmussen (1996), which could be derived from altered biogenic organic matter during diagenesis. ...